Spectrum-locked high-power volume Bragg grating external-cavity diode laser. (1st June 2022) - Zhang, Zhicheng; Pan, Huadong; Tan, Shaoyang; Yu, Hao; Liu, Wuling; Xiao, Yao; Wang, Bangguo; Zhou, Jun; Sun, Shujuan; Zhao, Wu; Gou, Yudan; Wang, Jun; et al.
Abstract: Spectrum-locked high-power diode lasers are extremely sought after in many fields. Here, we establish the volume Bragg grating external-cavity diode laser model and investigate the impact of facet reflectivity on the output spectrum. The simulation results emphasize that optimizing reflectivity can realize better spectrum-locking and side-mode suppression ratio. To prove the feasibility, we built a diode laser array with 20 single emitters. Three different facet reflectivity are prepared, 0.1%, 0.5%, and 0.8%. As a result, the output spectrums of the array are improved obviously with the decrease in reflectivity. In the case of 0.1%, the side-mode is well suppressed under injection current up to 16 A, and the calculated current-spectrum shift is around 0.07 nm A −1 . After beam combining and fiber coupling, an output power of 243.4 W and a brightness of about 11.2 MW cm −2 -str is attained.